The Effect of Various Drying Methods on the Quality of Rose (Rosa damascena) Tea - Karyadi, Joko Nugroho Wahyu; Imaniar, Dintia Ibni; Akbar, Muhammad Adani; Marfu’ah, Siti; Ayuni, Dwi; Bintoro, Nursigit (agriTECH, 2024)
Rose petals is potential ingredient for making a herbal tea. This study was aimed to determine the effect of various drying methods on the physical and chemical properties of the dried rose. The methods tested were freeze drying (FD), cabinet drying (CD), and sunlight drying (SM). Several properties included final moisture content, bulk density, shrinkage ratio, rehydration ratio, color difference, flavonoid content, and surface microstructure of dried petals were examined. The results showed that the best-fit model for the prediction of CD was the firstorder kinetic model, with a drying rate constant of 0.0494% d.b./h. Meanwhile, both FD and SM required zero and first-order kinetics to effectively explain the drying characteristics. The drying constant rates for zero-order and first-order kinetics were 39.544 and 0.12% d.b./h for FD as well as 70.6 and 0.413%d.b./h for SM, respectively. The final moisture content of dried rose produced by FD, CD, and SM was 5, 12, and 10% wet basis (w.b), respectively. Based on the Indonesian National Standard, the maximum moisture content of packaged dried tea is 8% w.b. FD successfully reduced the shrinkage ratio to a range of 0.35 – 0.45. Freeze-dried rose petals at 40 °C temperature resulted in the highest flavonoid content of 5.65 g QE/100 g sample. In conclusion FD was the best drying method for producing herbal tea from rose petals. This method could be adopted as a new alternative for producing high-quality healthy herbal tea.